2018
DOI: 10.1099/jmm.0.000820
|View full text |Cite
|
Sign up to set email alerts
|

Excess body weight and age associated with the carriage of fluoroquinolone and third-generation cephalosporin resistance genes in commensal Escherichia coli from a cohort of urban Vietnamese children

Abstract: The carriage of genotypic and phenotypic antimicrobial resistance is highly prevalent among E. coli in healthy children in the community in Vietnam. Future investigations on the carriage of antimicrobial resistant organisms in LMICs should focus on the progression of carriage from birth and structure of the microbiome in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Factors that were significantly associated with ESBL-Ec isolation (Figure 8) other than the risk factors for ESBL-E included environmental risk factors of staying in a rural region (aOR: 2.04, 95%CI: 1.3-3.2) as reported in a Vietnamese study (Trung et al, 2019). A study conducted among urban Vietnamese children also reported an inverse association with bla CTX−M gene carriage in older children (aOR: 0.97, 95%CI: 0.94-0.99) for each additional year (Thi Quynh Nhi et al, 2018).…”
Section: Risk Factors Associated With Extended-spectrum Beta-lactamase and Carbapenemase Isolationmentioning
confidence: 88%
“…Factors that were significantly associated with ESBL-Ec isolation (Figure 8) other than the risk factors for ESBL-E included environmental risk factors of staying in a rural region (aOR: 2.04, 95%CI: 1.3-3.2) as reported in a Vietnamese study (Trung et al, 2019). A study conducted among urban Vietnamese children also reported an inverse association with bla CTX−M gene carriage in older children (aOR: 0.97, 95%CI: 0.94-0.99) for each additional year (Thi Quynh Nhi et al, 2018).…”
Section: Risk Factors Associated With Extended-spectrum Beta-lactamase and Carbapenemase Isolationmentioning
confidence: 88%
“…On the other hand, the coexistence of ESBL genes CTX-M and QnrS was observed in E. coli isolates from 4 of 50 cases (8%) in the present study. Thi Quynh Nhi et al 29 revealed that Qnr and CTX-M genes coexisted in 52.2% of the samples from the Vietnamese population. Furthermore, QnrB and CTX-M coexisted in six isolates in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…For blood culture, an aliquot of 5-8 mL (for adults) or 2-5 mL (for children) of The rectal swabs/stools were sourced from two cohort studies. The first cohort involved 500 healthy children in Ho Chi Minh City, Vietnam, between 2014 and 2016 to longitudinally assess the incidence rate of dysentery 59 . Rectal swabs/stools from the final visit of each child were used for this study.…”
Section: Bacterial and Data Collectionmentioning
confidence: 99%